Mapping quasar light echoes in 3D with Ly alpha forest tomography - Schmidt, Tobias; Hennawi, Joseph F.; Lee, Khee-Gan; Lukić, Zarija; Oñorbe, Jose; White, Martin (The astrophysical journal, 2019)
The intense radiation emitted by luminous quasars dramatically alters the ionization state of their surrounding IGM. This so-called proximity effect extends out to tens of Mpc, and manifests as large coherent regions of enhanced Lyα (Lyα) forest transmission in absorption spectra of background sightlines. Here, we present a novel method based on Lyα forest tomography, which is capable of mapping these quasar “light echoes” in three dimensions. Using a dense grid (10-100) of faint () background galaxies as absorption probes, one can measure the ionization state of the IGM in the vicinity of a foreground quasar, yielding detailed information about the quasar’s radiative history and emission geometry. An end-to-end analysis—combining cosmological hydrodynamical simulations post-processed with a quasar emission model, realistic estimates of galaxy number densities, and instrument + telescope throughput—is conducted to explore the feasibility of detecting quasar light echoes. We present a new, fully Bayesian statistical method that allows one to reconstruct quasar light echoes from thousands of individual low-S/N transmission measurements. Armed with this tool, we undertake an exhaustive parameter study and show that light echoes can be convincingly detected for luminous (M 1450 < −27.5 mag, corresponding to m 1450 < 18.4 mag at ) quasars at redshifts 3 < z QSO 5) is sufficient, requiring three-hour integrations using existing instruments on 8 m class telescopes.